(untitled) (International Journal of Architecture and Urbanism, 2023)
The North Sumatra Athlete Hotel’s design with Ecological Architecture approach is intended to meet the need for supporting facilities in accommodating athletes who will compete in the upcoming XXI / 2024 national sports event (PON). This is a North Sumatra Province self-preparation form as one of the hosts in accommodating this event. The building design includes supporting facilities, outdoor and indoor sports facilities, a restaurant, and a convention centre. In terms of function, hotel building design and facilities are open to athletes and the public. In terms of the design theme, the theme approach is carried out through the application of concepts in the form of natural ventilation, natural lighting, shading with using vegetation, overhangs, balconies, and secondary skin which are applied through consideration of the orientation of the building to the incoming sunlight.